2010
DOI: 10.1016/j.jacc.2010.08.600
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Effect of the Combination of Ranolazine and Dronedarone to Suppress Atrial Fibrillation

Abstract: Objectives The aim of this study was to evaluate the effectiveness of a combination of dronedarone and ranolazine in suppression of atrial fibrillation (AF). Background Safe and effective pharmacological management of AF remains one of the greatest unmet medical needs. Methods The electrophysiological effects of dronedarone (10 μmol/l) and a relatively low concentration of ranolazine (5 μmol/l) separately and in combination were evaluated in canine isolated coronary-perfused right and left atrial and left … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
75
2
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(85 citation statements)
references
References 27 publications
7
75
2
1
Order By: Relevance
“…Additionally, ranolazine can be used on top of class III drugs as it has been shown that it does not cause pro‐arrhythmia despite a marked effect on ventricular repolarization 48, 49, 50. The beneficial role of ranolazine has also been demonstrated by experimental and human studies in atrial arrhythmias 10, 44, 51, 52, 53, 54, 55, 56, 57, 58, 59, 60, 61…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, ranolazine can be used on top of class III drugs as it has been shown that it does not cause pro‐arrhythmia despite a marked effect on ventricular repolarization 48, 49, 50. The beneficial role of ranolazine has also been demonstrated by experimental and human studies in atrial arrhythmias 10, 44, 51, 52, 53, 54, 55, 56, 57, 58, 59, 60, 61…”
Section: Discussionmentioning
confidence: 99%
“…However, the combination has been shown to have a dramatic effect beyond what would be expected by adding the effects of the 2 drugs. 51 This synergistic effect allows for lower dosing of dronedarone, thereby reducing its effect on cardiac contractility. In addition, the slowly activating delayed rectifier K+ current (I Ks ) becomes more dominant at high frequencies.…”
Section: Ranolazine+drondedaronementioning
confidence: 99%
“…Использование комбинации низких доз дронедарона и ранолазина для профилактики ре-цидива ФП изучалось в РКИ HARMONY (2014). В на-стоящее время ранолазин показан для лечения ста-бильной стенокардии, при этом подтверждена его способность предупреждать возникновение ФП, про-являя синергичный эффект при сочетании с амиода-роном или дронедароном [49]. Оба препарата пока не зарегистрированы в РФ [12].…”
Section: антиаритмическая терапия: трудный выбор при скудных возможноunclassified